Itaconic acid diglycidyl ester grafted elastomer compatilizer as well as preparation method and application thereof
By using diglycidyl itaconic acid as graft monomer, graft elastomer compatible agents with high epoxy value and high graft rate were prepared, and the existing GMA compatible agents were solved. The low epoxy value and grafting of grafts were solved. The problem of low rate significantly improves the toughness and interface compatibility of polyester materials.
Patent Information
- Application Number
- CN202411795829.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-14
AI Technical Summary
Among the existing polyester composite materials, glycidyl methacrylate (GMA) as a graft monomer has problems such as low epoxy value, low graft rate and general compatibility effect.
Itaconic acid diglycidyl ester (EIA) is used as graft monomer to prepare efficient Graft elastomer compatibility agent.
The epoxy value and grafting rate of the compatibility agent are improved, the toughness and strength of the polyester material are enhanced, and the interfacial compatibility and mechanical properties of the material are improved.
Smart Images

Figure CN119431691A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of compatibilizers and polymer composite materials, and particularly relates to a diglycidyl itaconate grafted elastomer compatibilizer and a preparation method and application thereof. Background Art
[0002] Polyester materials are polymer materials formed by the condensation of polyols and polyacids, such as PET, PEF and PBAT. Since polyester materials cannot take into account both material toughness and material rigidity, they often need to be compounded with toughening, reinforcing or rigidifying components. However, polyester often has interfacial compatibility issues with composite components, so a compatibilizer needs to be added to improve interfacial compatibility. Currently, the most widely used polyester composite material compatibilizer is glycidyl methacrylate (GMA) grafted elastomer compatibilizer, which can greatly improve the toughness and strength of polyester materials such as PET and PEF while improving the compatibility of composite materials.
[0003] However, GMA is not derived from bio-based materials, and its double bonds have a strong tendency to self-polymerize. It also has only one epoxy group and a low epoxy value. As a polar monomer for elastomer grafting compatibilizers, the prepared compatibilizers often have disadvantages such as low epoxy value, low grafting rate, and general compatibility. Therefore, it is of far-reaching value and significance to synthesize a monomer with bio-based sources, weak self-polymerization tendency, and multi-epoxy structure to replace traditional GMA as a grafting monomer, prepare high-efficiency elastomer compatibilizers, and apply them in polyester composites. Summary of the invention
[0004] The main purpose of the present invention is to provide a diglycidyl itaconate grafted elastomer compatibilizer and a preparation method and application thereof, so as to overcome the shortcomings of the prior art.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0006] The embodiment of the present invention provides a diglycidyl itaconate grafted elastomer compatibilizer. The raw materials for preparing the diglycidyl itaconate grafted elastomer compatibilizer include the following components: an elastomer, a peroxide initiator, diglycidyl itaconate and an active monomer; wherein the active monomer includes any one or more combinations of acrylamide, acrylic acid, butyl acrylate, α-methylstyrene and vinyl acetate.
[0007] The embodiment of the present invention also provides a method for preparing the aforementioned diglycidyl itaconate grafted elastomer compatibilizer, which comprises:
[0008] The elastomer, active monomer, peroxide initiator and diglycidyl itaconate are uniformly mixed, and then the obtained materials are input into a twin-screw extruder for melt blending, dynamic reaction extrusion and pelletizing to obtain diglycidyl itaconate grafted elastomer compatibilizer.
[0009] The embodiment of the present invention also provides the use of the aforementioned diglycidyl itaconate grafted elastomer compatibilizer in toughening polypropylene, nylon, polyester or engineering plastic alloy.
[0010] The embodiment of the present invention further provides a toughening compatibilizer, which at least includes the aforementioned diglycidyl itaconate grafted elastomer compatibilizer.
[0011] Compared with the prior art, the present invention has the following beneficial effects:
[0012] (1) The present invention uses diglycidyl itaconate synthesized from all bio-based sources as a grafting monomer to replace traditional glycidyl methacrylate, which has the advantages of low carbon and environmental protection, high epoxy value, low self-polymerization tendency and low odor;
[0013] (2) The present invention adopts the most conventional twin-screw extruder to carry out melt blending dynamic reaction, and the prepared EIA grafted elastomer compatibilizer has the advantages of high epoxy value, high grafting rate, low odor, high compatibility and low cost, especially the epoxy value can reach twice that of GMA grafted elastomer, and the grafting can reach nearly 1.5 times;
[0014] (3) Due to its high epoxy value and high grafting rate, the EIA grafted elastomer compatibilizer of the present invention can not only toughen materials such as polyester, polypropylene and nylon, but also have a very excellent effect of improving interfacial compatibility, thereby greatly improving the mechanical properties of the materials, such as impact strength and tensile strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0016] Figure 1 It is a trend diagram of the impact strength and elongation at break of the materials in the application examples and comparative examples of the present invention;
[0017] Figure 2 It is a trend diagram of tensile strength and tensile modulus of materials in application examples and comparative examples of the present invention. DETAILED DESCRIPTION
[0018] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Specifically, as one aspect of the technical solution of the present invention, it involves a diglycidyl itaconate grafted elastomer compatibilizer, and the raw materials for preparing the diglycidyl itaconate grafted elastomer compatibilizer include the following components: an elastomer, a peroxide initiator, diglycidyl itaconate and an active monomer; wherein the active monomer includes any one or more combinations of acrylamide, acrylic acid, butyl acrylate, α-methylstyrene and vinyl acetate.
[0020] In some preferred embodiments, the raw materials for preparing the diglycidyl itaconate grafted elastomer compatibilizer include the following components calculated in parts by mass: 100 parts of elastomer, 0.2-0.8 parts of peroxide initiator, and 2-10 parts of diglycidyl itaconate; wherein the mass ratio of the active monomer to the elastomer is 0.6-6:100.
[0021] In some preferred embodiments, the elastomer includes any one or more combinations of copolymers of butylene adipate and butylene terephthalate (PBAT), ethylene octene copolymer (POE), styrene-hydrogenated butadiene-styrene copolymer (SEBS), and olefin block copolymer (OBC), and is not limited thereto.
[0022] In some preferred embodiments, the peroxide initiator includes any one or more combinations of dicumyl peroxide (DCP), benzoyl peroxide (BPO), diisopropyl peroxydicarbonate (DIPP), and 1,4-di-tert-butylperoxyisopropylbenzene (BIBP), and is not limited thereto.
[0023] In some preferred embodiments, the method for preparing diglycidyl itaconate comprises:
[0024] Itaconic acid is reacted with a sodium source at room temperature to prepare sodium itaconate;
[0025] The sodium itaconate, epichlorohydrin, catalyst and anti-self-polymerization agent are mixed evenly, and then stirred at room temperature for 5 to 30 minutes in an inert gas, and then heated to 80 to 120° C. to react for 1 to 3 hours;
[0026] And, after the reaction is completed, the obtained product is washed with water and distilled under reduced pressure at 60-110° C. to obtain diglycidyl itaconate (EIA).
[0027] Furthermore, the sodium source includes any one or more combinations of sodium hydroxide, sodium carbonate, and sodium bicarbonate, but is not limited thereto.
[0028] Further, the catalyst includes any one or more combinations of benzyltriethylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium hydrogen sulfate, trioctylmethylammonium chloride, dodecyltrimethylammonium chloride, and tetradecyltrimethylammonium chloride, but is not limited thereto.
[0029] Further, the anti-self-polymerization agent includes any one or more combinations of p-benzoquinone, methylhydroquinone, p-hydroxyanisole, 2-tert-butylhydroquinone, and 2,5-di-tert-butylhydroquinone, but is not limited thereto.
[0030] Furthermore, the molar ratio of the itaconic acid to the sodium atoms in the sodium source is 1:1.
[0031] Furthermore, the mass ratio of the sodium itaconate, epichlorohydrin, catalyst and anti-self-polymerization agent is 100:600-1000:1-6:0.2-1.
[0032] Another aspect of the embodiments of the present invention further provides a method for preparing the aforementioned diglycidyl itaconate grafted elastomer compatibilizer, which comprises:
[0033] The elastomer, active monomer, peroxide initiator and diglycidyl itaconate are uniformly mixed, and then the obtained materials are input into a twin-screw extruder for melt blending, dynamic reaction extrusion and pelletizing to obtain diglycidyl itaconate grafted elastomer compatibilizer.
[0034] In some preferred embodiments, the process parameters adopted by the twin-screw extruder include: the temperature of zone 1 is 100-120°C, the temperature of zone 2 is 130-150°C, the temperature of zone 3 is 155-165°C, the temperatures of zones 4 to 5 are independently 170-180°C, the temperatures of zones 6 to 7 are independently 175-185°C, the temperatures of zones 8 to 9 are independently 185-195°C, the temperature of zone 10 is 175-185°C, the temperature of zone 11 is 170-180°C, the length-to-diameter ratio of the screw adopted is 42:1~52:1, and the screw speed is 200~400rpm.
[0035] In some more specific embodiments, the method for preparing the diglycidyl itaconate grafted elastomer compatibilizer comprises the following steps:
[0036] a. After the elastomer and the dispersed oil are uniformly mixed according to the aforementioned mass fractions, the initiator and EIA are added and mixed again;
[0037] b. Add the material of step a to a twin-screw extruder for melt blending and dynamic reaction extrusion, wherein the process parameters adopted by the twin-screw extruder include: a temperature of zone 1 of 100-120°C, a temperature of zone 2 of 130-150°C, a temperature of zone 3 of 155-165°C, temperatures of zones 4 to 5 are independently 170-180°C, temperatures of zones 6 to 7 are independently 175-185°C, temperatures of zones 8 to 9 are independently 185-195°C, temperatures of zone 10 are 175-185°C, temperatures of zone 11 are 170-180°C, a screw aspect ratio of 42:1-52:1 is adopted for the twin-screw melt extrusion, and a screw speed of 200-400rpm;
[0038] c. The extruded material is cooled by circulating water in a cooling water tank and cut into particles of uniform size by a pelletizer.
[0039] Another aspect of the embodiments of the present invention further provides the use of the aforementioned diglycidyl itaconate grafted elastomer compatibilizer in toughening polypropylene, nylon, polyester or engineering plastic alloy.
[0040] Another aspect of the embodiments of the present invention further provides a toughening compatibilizer, which at least includes the aforementioned diglycidyl itaconate grafted elastomer compatibilizer.
[0041] The diglycidyl itaconate grafted elastomer compatibilizer provided by the present invention is used in polymer composite materials such as elastomer toughened polypropylene, glass fiber reinforced nylon, elastomer toughened polyester and engineering plastic alloy. While playing a toughening effect, it greatly improves the interface compatibility of the composite material and prevents the interface separation of the composite material, thereby greatly improving the mechanical properties of the polymer composite material.
[0042] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0043] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0044] The diglycidyl itaconate used in the following examples was prepared by the following method:
[0045] According to the mass fraction, 100 parts of itaconic acid and sodium hydroxide in the same molar ratio are prepared into sodium itaconate at room temperature. After 100 parts of sodium itaconate, 800 parts of epichlorohydrin, 4 parts of tetrabutylammonium bromide (TBAB) and 0.5 parts of methylhydroquinone are evenly mixed, under the protection of inert gas, the mixture is vigorously stirred at room temperature for 30 minutes and then heated to 115°C and reacted for 2 hours; then the mixture is cooled to room temperature and the obtained components are washed with water, and diglycidyl itaconate is obtained after reduced pressure distillation at 90°C. The synthesized EIA has an epoxy value of 0.825 and a yield of 84.1%.
[0046] The process parameters adopted by the twin-screw extruder in the following embodiments include: the temperature of zone 1 is 110°C, the temperature of zone 2 is 140°C, the temperature of zone 3 is 160°C, the temperatures of zones 4 to 5 are independently 175°C, the temperatures of zones 6 to 7 are independently 180°C, the temperatures of zones 8 to 9 are independently 190°C, the temperature of zone 10 is 180°C, and the temperature of zone 11 is 175°C.
[0047] Example 1
[0048] According to the following mass parts: 100 parts of SEBS, 0.6 parts of α-methylstyrene, 0.5 parts of BIBP, and 2 parts of EIA were uniformly mixed and added into a twin-screw extruder for melt blending reaction extrusion. The screw length-diameter ratio of the twin-screw melt extrusion was 48:1, and the screw speed was 300 rpm. After extrusion, water cooling and granulation were performed. After homogenization, high-efficiency compatibilizer particles (referred to as: EIA-g-SEBS) were obtained. The epoxy value of the compatibilizer measured after purification was 0.423*10 -2 , the grafting rate is 0.523%.
[0049] Example 2
[0050] The following mass parts: 100 parts of SEBS, 1.8 parts of α-methylstyrene, 0.5 parts of BIBP, and 6 parts of EIA were uniformly mixed and added into a twin-screw extruder for melt blending reaction extrusion. The screw length-diameter ratio of the twin-screw melt extrusion was 48:1, and the screw speed was 300 rpm. After extrusion, water cooling and granulation were performed. After homogenization, high-efficiency compatibilizer particles (referred to as: EIA-g-SEBS) were obtained. The epoxy value of the compatibilizer measured after purification was 1.53*10 -2 , the grafting rate is 1.851%.
[0051] Example 3
[0052] The following mass parts: 100 parts of SEBS, 3 parts of α-methylstyrene, 0.5 parts of BIBP, and 10 parts of EIA were uniformly mixed and added into a twin-screw extruder for melt blending reaction extrusion. The screw length-diameter ratio of the twin-screw melt extrusion was 48:1, and the screw speed was 300 rpm. After extrusion, water cooling and granulation were performed. After homogenization, high-efficiency compatibilizer particles (referred to as: EIA-g-SEBS) were obtained. The epoxy value of the compatibilizer measured after purification was 1.486*10 -2 , the grafting rate is 1.798%.
[0053] Example 4
[0054] The following mass parts: 100 parts of SEBS, 1.8 parts of α-methylstyrene, 0.2 parts of BIBP, and 6 parts of EIA were uniformly mixed and added into a twin-screw extruder for melt blending reaction extrusion. The screw length-diameter ratio of the twin-screw melt extrusion was 48:1, and the screw speed was 300 rpm. After extrusion, water cooling and granulation were performed. After homogenization, high-efficiency compatibilizer particles (referred to as: EIA-g-SEBS) were obtained. The epoxy value of the compatibilizer measured after purification was 0.671*10 -2 , the grafting rate is 0.812%.
[0055] Example 5
[0056] The following mass parts: 100 parts of SEBS, 1.8 parts of α-methylstyrene, 0.8 parts of BIBP, and 6 parts of EIA were uniformly mixed and added into a twin-screw extruder for melt blending reaction extrusion. The screw length-diameter ratio of the twin-screw melt extrusion was 48:1, and the screw speed was 300 rpm. After extrusion, water cooling and granulation were performed. After homogenization, high-efficiency compatibilizer particles (referred to as: EIA-g-SEBS) were obtained. The epoxy value of the compatibilizer measured after purification was 1.324*10 -2 , the grafting rate is 1.602%.
[0057] Example 6
[0058] The following mass parts: 100 parts of SEBS, 1.8 parts of α-methylstyrene, 0.8 parts of DCP, and 6 parts of EIA were uniformly mixed and added into a twin-screw extruder for melt blending reaction extrusion. The screw length-diameter ratio of the twin-screw melt extrusion was 48:1, and the screw speed was 300 rpm. After extrusion, water cooling and granulation were performed. After homogenization, high-efficiency compatibilizer particles (referred to as: EIA-g-SEBS) were obtained. The epoxy value of the compatibilizer measured after purification was 1.215*10 -2 , the grafting rate is 1.47%.
[0059] Example 7
[0060] The following mass parts: 100 parts of SEBS, 6 parts of α-methylstyrene, 0.8 parts of BPO, and 6 parts of EIA were uniformly mixed and added into a twin-screw extruder for melt blending reaction extrusion. The screw length-diameter ratio of the twin-screw melt extrusion was 48:1, and the screw speed was 300 rpm. After extrusion, water cooling and granulation were performed. After homogenization, high-efficiency compatibilizer particles (referred to as: EIA-g-SEBS) were obtained. The epoxy value of the compatibilizer measured after purification was 1.135*10 -2 , the grafting rate is 1.373%.
[0061] Example 8
[0062] The following mass parts: 100 parts of SEBS, 1.8 parts of acrylamide, 0.8 parts of BIBP, and 6 parts of EIA were uniformly mixed and added into a twin-screw extruder for melt blending reaction extrusion. The screw length-diameter ratio of the twin-screw melt extrusion was 48:1, and the screw speed was 300 rpm. After extrusion, water cooling and granulation were performed. After homogenization, high-efficiency compatibilizer particles (referred to as: EIA-g-SEBS) were obtained. The epoxy value of the compatibilizer measured after purification was 1.768*10 -2 , the grafting rate is 2.139%.
[0063] Comparative Example 1
[0064] The following mass parts: 100 parts of SEBS, 1.8 parts of α-methylstyrene, 0.5 parts of BIBP, and 6 parts of GMA were uniformly mixed and added into a twin-screw extruder for melt blending reaction extrusion. The screw length-diameter ratio of the twin-screw melt extrusion was 48:1, and the screw speed was 300 rpm. After extrusion, water cooling and granulation were performed. After homogenization, high-efficiency compatibilizer particles (referred to as: GMA-g-SEBS compatibilizer) were obtained. The epoxy value of the compatibilizer measured after purification was 0.632*10 -2 , the grafting rate is 1.898%.
[0065] Comparative Example 2
[0066] The method is the same as in Example 2, except that α-methylstyrene is absent.
[0067] Comparative Example 3
[0068] The method is the same as Example 2, except that: 15 parts of EIA, elastomer cross-linking occurs during melt extrusion, making the material unable to be extruded.
[0069] Comparison of Comparative Example 1 with Examples 1-8 shows that the epoxy value and grafting rate of the final compatibilizer using EIA as the grafting monomer are generally higher than the epoxy value of GMA as the grafting monomer, which is closely related to the diepoxy structure of EIA and its low tendency to self-polymerization. At the same time, it can be seen from Examples 1-5 that using BIBP as the initiator, Example 2 is the best grafting scheme. At the same time, it can be seen from Examples 6-8 that PBAT, POE and OBC as grafted elastomers can also obtain epoxy values higher than 1.1*10 -2 and an EIA grafted elastomer compatibilizer having a grafting rate greater than 1.3%.
[0070] The raw materials, process parameters and performances used in Examples 1-8 and Comparative Example 1 are shown in Table 1:
[0071] Table 1
[0072]
[0073] Application Example 1
[0074] 100 parts of polyethylene 2,5-furandicarboxylate (PEF), 19 parts of SEBS, 1 part of EIA-g-SEBS (Example 2), and 0.15 parts of antioxidants 1010 and 168 were uniformly mixed by mass, and then added to the main feeding hopper of a twin-screw extruder for melt blending, extrusion and granulation. The screw speed was adjusted to 300 RPM and the main feeding speed to 70 RPM, and the melt blending extrusion temperature was 190-230 ° C to obtain a SEBS toughened PEF material.
[0075] Application Example 2
[0076] 100 parts of polyethylene 2,5-furandicarboxylate (PEF), 18 parts of SEBS, 2 parts of EIA-g-SEBS (Example 2), and 0.15 parts of antioxidants 1010 and 168 were uniformly mixed by mass, and then added to the main feeding hopper of a twin-screw extruder for melt blending, extrusion and granulation. The screw speed was adjusted to 300 RPM and the main feeding speed to 70 RPM, and the melt blending extrusion temperature was 190-230 ° C to obtain a SEBS toughened PEF material.
[0077] Application Example 3
[0078] 100 parts of polyethylene 2,5-furandicarboxylate (PEF), 16 parts of SmBS, 4 parts of EIA-g-SEBS (Example 2), and 0.15 parts of antioxidants 1010 and 168 were uniformly mixed by mass, and then added to the main feeding hopper of a twin-screw extruder for melt blending, extrusion and granulation. The screw speed was adjusted to 300 rpm and the main feeding speed to 70 rpm, and the melt blending extrusion temperature was 190-230 ° C to obtain a SEBS toughened PEF material.
[0079] Application Example 4
[0080] 100 parts of polyethylene 2,5-furandicarboxylate (PEF), 14 parts of SEBS, 6 parts of EIA-g-SEBS (Example 2), and 0.15 parts of antioxidants 1010 and 168 were uniformly mixed by mass, and then added to the main feeding hopper of a twin-screw extruder for melt blending, extrusion and granulation. The screw speed was adjusted to 300 rpm and the main feeding speed to 70 rpm, and the melt blending extrusion temperature was 190-230 ° C to obtain a SEBS toughened PEF material.
[0081] Application Example 5
[0082] 100 parts of polyethylene 2,5-furandicarboxylate (PEF), 10 parts of SEBS, 10 parts of EIA-g-SEBS (Example 2), and 0.15 parts of antioxidants 1010 and 168 were uniformly mixed by mass, and then added to the main feeding hopper of a twin-screw extruder for melt blending, extrusion and granulation. The screw speed was adjusted to 300 rpm and the main feeding speed was adjusted to 70 rpm. The melt blending extrusion temperature was 190-230 ° C to obtain a SEBS toughened PEF material.
[0083] Application Comparative Example 1
[0084] 100 parts of polyethylene 2,5-furandicarboxylate (PEF), 20 parts of SEBS (the same as in the embodiment), and 0.15 parts of antioxidants 1010 and 168 were uniformly mixed by mass, and then added to the main feeding hopper of a twin-screw extruder for melt blending, extrusion and granulation. The screw speed was adjusted to 300 rpm and the main feeding speed to 70 rpm, and the melt blending extrusion temperature was 190-230 ° C to obtain a SEBS toughened PEF material.
[0085] Application Comparative Example 2
[0086] The method is the same as that of comparative example 1, except that the PEF is not toughened and a compatibilizer is not added.
[0087] Application Comparative Example 3
[0088] The method is the same as that of Application Example 2, except that the GMA-g-SEBS compatibilizer prepared in Comparative Example 1 is used to replace EIA-g-SEBS, that is, 18 parts of SEBS and 2 parts of GMA-g-SEBS are added.
[0089] Application Comparative Example 4
[0090] The method is the same as that of Application Example 2, except that: the compatibilizer without the third monomer prepared in Comparative Example 2 is used to replace EIA-g-SEBS in the same proportion;
[0091] Figure 1The impact strength and elongation at break trend diagram of the materials in Application Examples 1-5 and Application Comparative Examples 1-4 of the present invention show that, in comparison between pure PEF and SEBS-toughened PEF, the addition of EIA-g-SEBS can effectively improve the compatibility between SEBS and PEF, thereby improving the toughening effect of PEF materials, and improving the impact strength and elongation at break of PEF. However, if the amount of compatibilizer added is too large, the relevant properties will be reduced. And from the comparison between Comparative Examples 3-4 and Application Example 2, it can be seen that the toughening and compatibilization effect of EIA-g-SEBS is significantly better than that of GMA-g-SEBS and EIA-g-SEBS without the addition of a third monomer.
[0092] Figure 2 It is a trend diagram of the tensile properties of the materials in Application Examples 1-5 and Comparative Application Examples 1-4 of the present invention. It can be seen from the figure that, compared with pure PEF and SEBS toughened PEF, the tensile strength is significantly improved after adding EIA-g-SBES, and the tensile modulus decreases accordingly due to toughening compatibility. At the same time, the toughening effect of GMA-g-SBES and the solution without adding a third monomer compatibilizer is worse than that of EIA-g-SEBS.
[0093] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0094] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A diglycidyl itaconate grafted elastomer compatibilizer, characterized in that: The raw materials for preparing the diglycidyl itaconate grafted elastomer compatibilizer include the following components: elastomer, peroxide initiator, diglycidyl itaconate and active monomers; wherein the active monomers include any one or more combinations of acrylamide, acrylic acid, butyl acrylate, α-methylstyrene and vinyl acetate.
2. The diglycidyl itaconate grafted elastomer compatibilizer according to claim 1, characterized in that: The raw materials for preparing the diglycidyl itaconate grafted elastomer compatibilizer include the following components calculated by mass: 100 parts of elastomer, 0.2-0.8 parts of peroxide initiator, and 2-10 parts of diglycidyl itaconate; wherein the mass ratio of the active monomer to the elastomer is 0.6-6:
100.
3. The diglycidyl itaconate grafted elastomer compatibilizer according to claim 1, characterized in that: The elastomer includes any one or more combinations of a copolymer of butylene adipate and butylene terephthalate, an ethylene octene copolymer, a styrene-hydrogenated butadiene-styrene copolymer, and an olefin block copolymer.
4. The diglycidyl itaconate grafted elastomer compatibilizer according to claim 1, characterized in that: The peroxide initiator includes any one or more combinations of dicumyl peroxide, benzoyl peroxide, diisopropyl peroxydicarbonate, and 1,4-di-tert-butyl peroxycumene.
5. The diglycidyl itaconate grafted elastomer compatibilizer according to claim 1, characterized in that: The preparation method of diglycidyl itaconate comprises: Itaconic acid is reacted with a sodium source at room temperature to prepare sodium itaconate; The sodium itaconate, epichlorohydrin, catalyst and anti-self-polymerization agent are mixed evenly, and then stirred at room temperature for 5 to 30 minutes in an inert gas, and then heated to 80 to 120° C. to react for 1 to 3 hours; And, after the reaction is completed, the obtained product is washed with water and distilled under reduced pressure at 60-110° C. to obtain diglycidyl itaconate.
6. The diglycidyl itaconate grafted elastomer compatibilizer according to claim 5, characterized in that: The sodium source includes any one or more combinations of sodium hydroxide, sodium carbonate, and sodium bicarbonate; And / or, the catalyst includes any one or more combinations of benzyltriethylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium hydrogen sulfate, trioctylmethylammonium chloride, dodecyltrimethylammonium chloride, and tetradecyltrimethylammonium chloride; And / or, the anti-self-polymerization agent includes any one or more combinations of p-benzoquinone, methylhydroquinone, p-hydroxyanisole, 2-tert-butylhydroquinone, and 2,5-di-tert-butylhydroquinone.
7. The method for preparing the diglycidyl itaconate grafted elastomer compatibilizer according to any one of claims 1 to 6, characterized in that: include: The elastomer, active monomer, peroxide initiator and diglycidyl itaconate are uniformly mixed, and then the obtained materials are input into a twin-screw extruder for melt blending, dynamic reaction extrusion and pelletizing to obtain diglycidyl itaconate grafted elastomer compatibilizer.
8. The preparation method according to claim 7, characterized in that: The process parameters adopted by the twin-screw extruder include: the temperature of zone 1 is 100-120°C, the temperature of zone 2 is 130-150°C, the temperature of zone 3 is 155-165°C, the temperatures of zones 4 to 5 are independently 170-180°C, the temperatures of zones 6 to 7 are independently 175-185°C, the temperatures of zones 8 to 9 are independently 185-195°C, the temperature of zone 10 is 175-185°C, the temperature of zone 11 is 170-180°C, the length-to-diameter ratio of the screw adopted is 42:1-52:1, and the screw speed is 200-400rpm.
9. Use of the diglycidyl itaconate grafted elastomer compatibilizer according to any one of claims 1 to 6 in toughening polypropylene, nylon, polyester or engineering plastic alloy.
10. A toughening compatibilizer, characterized in that: The invention comprises at least the diglycidyl itaconate grafted elastomer compatibilizer according to any one of claims 1 to 6.